Randomness Tests On Nine Data Categories Of RECTANGLE Using NIST Statistical Test Suite - Abdul Alif Zakaria; Nur Hafiza Zakaria; Maslina Daud; Azni Hazlizan Ab Halim; Farida Hazwani Mohd Ridzuan (Malaysian Society for Cryptology Research, Universiti Putra Malaysia, 2024)
Volume 10 Issue (2) (July - December 2020)